The clinical advantage of nasal high-flow in respiratory management during procedural sedation: A scoping review on the application of nasal high-flow during dental procedures with sedation - Shinji Kurata; Takuro Sanuki; Hitoshi Higuchi; Takuya Miyawaki; Seiji Watanabe; Shigeru Maeda; Shuntaro Sato; Max Pinkham; Stanislav Tatkov; Takao Ayuse (Elsevier, 2022)
Structured summary: Rationale: Nasal high-flow (NHF), a new method for respiratory management during procedural sedation, has greater advantages than conventional nasal therapy with oxygen. However, its clinical relevance for patients undergoing oral maxillofacial surgery and/or dental treatment remains uncertain and controversial, due to a paucity of studies. This scoping review compared and evaluated NHF and conventional nasal therapy with oxygen in patients undergoing oral maxillofacial surgery and/or dental treatment. Materials and methods: A literature search of two public electronic databases was conducted, and English writing randomized controlled trials (RCTs) of nasal high flow during dental procedure with sedation reviewed. The primary and secondary outcomes of interest were the incidence of hypoxemia and hypercapnia during sedation and the need for intervention to relieve upper airway obstruction, respectively. Results: The search strategy yielded 7 studies, of which three RCTs met our eligibility criteria, with a total of 78 patients. Compared with conventional nasal therapy with oxygen, NHF significantly reduced the incidence of hypoxemia and hypercapnia during procedural sedation. Conclusion: NHF can maintain oxygenation and possibly prevent hypercapnia in patients undergoing dental treatment. Additional RCTs are needed to clarify and confirm these findings.